The output effect of fiscal consolidation plans - Alberto Alesina; Carlo Favero; Francesco Giavazzi (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
We show that the correct experiment to evaluate the effects of a fiscal adjustment is the simulation of a multi year fiscal plan rather than of individual fiscal shocks. Simulation of fiscal plans adopted by 16 OECD countries over a 30-year period supports the hypothesis that the effects of consolidations depend on their design. Fiscal adjustments based upon spending cuts are much less costly, in terms of output losses, than tax-based ones and have especially low output costs when they consist of permanent rather than stop and go changes in taxes and spending. The difference between tax-based and spending-based adjustments appears not to be explained by accompanying policies, including monetary policy. It is mainly due to the different response of business confidence and private investment.
urn:nbn:de:hebis:30:3-361347
Keywords: H60; E62; 330; confidence; fiscal adjustment; investment